Investigation of 1h NMR profile of vegetarian human urine using anova-based multi-factor analysis - Dong, J. Y. (Jilin Daxue,Jilin University, 2011)
In this study,a technique that combined both analysis of variance(ANOVA) and partial least squares-discriminant analysis(PLS-DA) was used to compare the urine 1H NMR spectra of healthy people from a vegetarian and omnivorous population.In ANOVA/PLS-DA,the variation in data was first decomposed into different variance components that each contains a single source of variation.Each of the resulting variance components was then analyzed using PLS-DA.The experimental results showed that ANOVA/PLS-DA is efficient in disentangling the effect of diet and gender on the metabolic profile,and the method could be used to extract biologically relevant information for result interpretation.